2016
DOI: 10.4184/asj.2016.10.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Lumbar Foraminal Stenosis using Diffusion Tensor Imaging

Abstract: Diagnosis of lumbar foraminal stenosis remains difficult. Here, we report on a case in which bilateral lumbar foraminal stenosis was difficult to diagnose, and in which diffusion tensor imaging (DTI) was useful. The patient was a 52-year-old woman with low back pain and pain in both legs that was dominant on the right. Right lumbosacral nerve compression due to a massive uterine myoma was apparent, but the leg pain continued after a myomectomy was performed. No abnormalities were observed during nerve conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…DTI may reveal the local lumbar nerve damage. 38 There are several limitations to this study. First, only a few patients were investigated.…”
Section: Fig 3bmentioning
confidence: 94%
See 1 more Smart Citation
“…DTI may reveal the local lumbar nerve damage. 38 There are several limitations to this study. First, only a few patients were investigated.…”
Section: Fig 3bmentioning
confidence: 94%
“…Recently we found that there were no abnormalities in either amplitude or nerve conduction velocity in the tibial or peroneal nerves in patients with L5 foraminal stenosis. 38 Nerve conduction studies are tests that are used to detect nerve conduction disorders peripheral to the knee, but lumbar nerve injuries are localised to the spinal canal, and if Waller degeneration does not extend to the region below the knee, then there is the possibility of falsenegative findings. The changes in DTI parameters indicating neuropathy were dependent on the site of nerve compression.…”
Section: Fig 3bmentioning
confidence: 99%
“…A total of 683 subjects were studied across 24 DTI articles. 177 patients with lumbar spinal canal stenosis (LSCS) in 5 articles 11,12,16,17,20) , 143 patients with lumbar disc herniation (LDH) in 7 articles 7,13,15,20,21,23,29) , 112 patients with lumbar radiculopathy in 3 articles 10,19,22) , 36 patients with foraminal stenosis (FS) in 6 articles 9,11,16,20,27,28) , 2 patients with lower back pain in one article 20) , 3 cases with diastematomyelia and one case with tethered cord in one article 30) , and one case with spina bifida in one article 26) were included. 7 post mortem subjects were investigated in one article 8) .…”
Section: Diffusion-weighted Mr Neurographymentioning
confidence: 99%
“…All 17 articles 7,[9][10][11][12][13][15][16][17]19,20,22,23,[27][28][29][30] . Except for one continued.…”
Section: Measurement Of Dti Parametersmentioning
confidence: 99%
See 1 more Smart Citation